PENERAPAN MODEL PEMBELAJARAN WRITE AROUND UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN BERBANTUAN MEDIA FILM DI SEKOLAH DASAR - Warda Ningsih; Yenni Fitra Surya; Yanti Yandri Kusuma; Ramdhan Witarsa; Nurhaswinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This implementation was motivated by the low narrative writing skills of students in the Indonesian language subject at SDN 006 Pasir Sialang, Bangkinang District, Kampar Regency. One solution to overcome this problem is to apply the Write Around learning model. The purpose of this study is to describe the application of the Write Around learning model to improve the skills of writing narrative essays assisted by picture media. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection, and research time from May 2025. The subjects of this study were 25 class V students, with 15 boys and 10 girls. Collection techniques in the form of documentation, observation and tests. The results of the study can be concluded that the skill of writing narrative essays using the Write Around learning model for class V SDN 006 Pasir Sialang in cycle I was classified as good with an average of 76,96. Furthermore, of the 25 students, only 21 students completed the classical learning completeness, while 84%. In cycle II it was very good with an average of 88, and out of 25 students there were 25 people who completed it while the classical learning mastery was 100%. Thus it can be concluded that using the Write Around learning model can improve the skills of writing narrative essays for class V SDN 006 Pasir Sialang.